The effect of capital structure on profitability of selected firms listed on the Ghana stock exchange. - Nketia, Jacinta (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partial Fulfillment Of The Requirement For The Degree Of Master Of Business Administration (Finance-Option).